EFEITO DA MATRICARIA CHAMOMILLA CH12 NA RESPOSTA DE ESTRESSE EM CÃES - Renata Navarro Cassu; Cibele Damião Andreazi; Liliane Pereira (Colloquium Agrariae, 2011)
This study aimed to evaluate the stress response, in female dogs after social isolation and undergoing ovariohysterectomy. Eighteen adult, healthy female dogs were distributed in two treatments groups: TP (n=9), placebo was administered and TC (n = 9), was administered Matricaria chamomilla CH12. Both treatments were administered during 15 days before the surgery and maintained for 24 hours postoperative. Behaviors were evaluated during social isolation. Serum cortisol concentration was evaluated before placebo or Matricaria chamomilla treatments administration (M0), 15 days after treatments dministration (M1), immediately after the surgery (M2) and 24 hours postoperative (M3). There was significant difference in the serum cortisol concentration between the groups immediately after the surgery (M1), with higher values in TP. It was conclude that the treatment with Matricaria chamomilla CH12 prevented the post surgical stress, maintaining stable the serum cortisol concentration.